2014
DOI: 10.1007/s13355-014-0293-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the veterinary antiparasitic drug eprinomectin on dung beetles (Coleoptera: Scarabaeidae), the non-pest fly Neomyia cornicina and pest fly Haematobia irritans (Diptera: Muscidae) in Japan

Abstract: Effects of the antiparasitic drug eprinomectin were studied in the laboratory and field experiments in Hokkaido, Japan, by pour-on administrations (500 lg/kg) on the pest fly Haematobia irritans (Linnaeus), nontarget coprophagous fly Neomyia cornicina (Fabricius), and the dung beetles Caccobius jessoensis Harold and Liatongus minutus (Motschulsky). Eprinomectin excreted into cattle dung was highest at 3 days post-treatment in both experiments, then it declined rapidly at 7 days and was not detected on or after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 38 publications
1
11
2
Order By: Relevance
“…In previously published studies eprinomectin pour-on formulation was found to cause dung contamination for 1-29 days post-treatment with a peak at 2 or 3 days post-treatment (Lumaret et al, 2005;Iwasa & Sugitani, 2014). Present results which showed a peak at 1 day post-treatment are different from those of above literatures.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In previously published studies eprinomectin pour-on formulation was found to cause dung contamination for 1-29 days post-treatment with a peak at 2 or 3 days post-treatment (Lumaret et al, 2005;Iwasa & Sugitani, 2014). Present results which showed a peak at 1 day post-treatment are different from those of above literatures.…”
Section: Discussioncontrasting
confidence: 94%
“…Moreover, there were no brood balls and/or oviposition of C. acutidens and C. ochus in dung from ivermectin-treated cattle at 1 day after treatment (Iwasa et al, 2007). In dung from eprinomectintreated cattle, there was no effect on the number of brood balls of C. jessoensis and L. minutus (Iwasa & Sugitani, 2014).…”
Section: Controlmentioning
confidence: 90%
“…Reduced survival has been reported for Onthophagus taurus (Schreber) developing in dung of cattle treated up to 14 d previously with a topical application of eprinomectin [ 29 ]. Adult emergence of Caccobius jessoenisis (Harold) was suppressed in dung of cattle injected with a recommended dose of eprinomectin up to 3 d previously, but not 7 d previously, by which time eprinomectin concentrations declined to approximately 50 ng g -1 wet weight [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…In laboratory studies, survival of Neomyia cornicina (Fabricius) and H . irritans was reduced in dung from cattle treated 12 and 14 d previously with a topical application of eprinomectin [ 7 , 29 , 90]. Reduced survival of N .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation